2011
DOI: 10.47102/annals-acadmedsg.v40n4p160
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Development of New-onset Diabetes after Kidney Transplantation

Abstract: Introduction: New-onset diabetes after transplantation (NODAT) is an increasingly recognised metabolic complication of kidney transplantation that is associated with increased morbidity and mortality. This study aimed to determine the incidence of NODAT and identify risk factors for development of NODAT among kidney allograft recipients in a single centre. Materials and Methods: We retrospectively reviewed all kidney allograft recipients in our centre between 1998 and 2007. NODAT were determined using criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This study found that the incidence of NODAT among kidney recipients was 38.3%, which is similar to that reported from Bahrain (33.5%), 26 and India (33.85%). 27 Nevertheless, it is more often higher than in other Arab countries, 28 29 30 Japan, 31 France, 32 the United States, 5 Russia, 33 Singapore, 34 and Canada. 35 The rates in these countries ranged between 7 and 24.2%.…”
Section: Discussionmentioning
confidence: 97%
“…This study found that the incidence of NODAT among kidney recipients was 38.3%, which is similar to that reported from Bahrain (33.5%), 26 and India (33.85%). 27 Nevertheless, it is more often higher than in other Arab countries, 28 29 30 Japan, 31 France, 32 the United States, 5 Russia, 33 Singapore, 34 and Canada. 35 The rates in these countries ranged between 7 and 24.2%.…”
Section: Discussionmentioning
confidence: 97%
“…Although none of the patients in this small series developed new diabetes after transplantation, previous local studies have reported a high incidence of diabetes (24.2%) at 5 years post-KT, which was associated with poorer graft and patient survival rates. 22 Thus, managing physicians should remain alert to the potential need to intensify diabetes treatment after transplant, even if patients experience improvements or normalization of blood glucose after bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[33] Older age was observed as the risk factor for NODAT in populations of Brazil, [34] Turkey, [35] Portugal, [36] South Africa, [37] and Singapore. [38] Cosio et al [6] reported that there was 2.9 times increased risk in individuals undergoing renal transplantation, of age >45 years than younger patients. Gourishankar et al [39] have reported 1.5 times more risk for developing NODAT for every decade increase in life.…”
Section: Discussionmentioning
confidence: 99%